Tuning the C1/C2 Selectivity of Electrochemical CO2 Reduction on Cu–CeO2 Nanorods by Oxidation State Control. Issue 8 (20th December 2022) - Hong, Seungwon; Abbas, Hafiz Ghulam; Jang, Kyuseon; Patra, Kshirodra Kumar; Kim, Beomil; Choi, Byeong‐Uk; Song, Hakhyeon; Lee, Kug‐Seung; Choi, Pyuck‐Pa; Ringe, Stefan; Oh, Jihun
Abstract : Ceria (CeO2 ) is one of the most extensively used rare earth oxides. Recently, it has been used as a support material for metal catalysts for electrochemical energy conversion. However, to date, the nature of metal/CeO2 interfaces and their impact on electrochemical processes remains unclear. Here, a Cu–CeO2 nanorod electrochemical CO2 reduction catalyst is presented. Using operando analysis and computational techniques, it is found that, on the application of a reductive electrochemical potential, Cu undergoes an abrupt change in solubility in the ceria matrix converting from less stable randomly dissolved single atomic Cu 2+ ions to (Cu 0, Cu 1+ ) nanoclusters. Unlike single atomic Cu, which produces C1 products as the main product during electrochemical CO2 reduction, the coexistence of (Cu 0, Cu 1+ ) clusters lowers the energy barrier for C–C coupling and enables the selective production of C2+ hydrocarbons. As a result, the coexistence of (Cu 0, Cu 1+ ) in the clusters at the Cu–ceria interface results in a C2+ partial current density/unit Cu weight 27 times that of a corresponding Cu‐carbon catalyst under the same conditions. Abstract : S. Hong, H. G. Abbas, K. Jang, K. K. Patra, B. Kim, B.‐U. Choi, H. Song, K.‐S. Lee, P.‐P. Choi, S. Ringe, J. Oh The tunable CH4 /C2 H4 selectivity of Cu–CeO2 nanorods during the electrochemical CO2 reduction reaction by precisely controlling the structure and valence state of the Cu active sites on CeO2 nanorods is reported. The coexistence of (Cu 0, Cu 1+ ) clusters on ceria nanorods lowers the energy barrier for C–C coupling and enables the selective production of C2+ hydrocarbons.